An Analysis of Scotland’s Post-COVID Media Graduate Landscape - James Patrick Mahon (Journalism and Media)
This article explores the challenges surrounding the Scottish media graduate landscape after the COVID-19 pandemic. Contributing factors that impact Scotland-based students and educators include a shift in the jobs market, altering pedagogies during and post-pandemic, and social drivers including fewer students choosing media pathways of study due to the cost-of-living crisis. This study draws on insights from 40 students at five Scottish universities, all of whom graduated in the summer of 2023. The research presents a window into the mindset and expectations of this post-pandemic graduating class while drawing on current and relevant literature. In addition, the paper includes reaction from industry and academic experts in Scotland and questions what can be done to address trends surrounding the stability and sustainability of journalism education. The experts include senior broadcasters, an established media educator who has worked across further education and higher education in Scotland while also being a national news editor, and one of Scotland’s most experienced journalism educators who is the chair of the World Journalism Education Council. This work is predominantly qualitative, drawing on a mixed research approach of expert interviewing and surveys while providing recommendations for journalism educators.